Criminal defense work in a sample of arrest hearings in three states of Mexico: the micro-dynamics of case-level engagement, influence, and strategy - Rengifo, Andres F. (Crime, law and social change, 2023)
We examine variation in criminal defense work in a sample of arrest hearings in three states of Mexico (N = 186). Specifically, drawing on systematic observations, we map the explicit challenges voiced by counsel to oppose motions by prosecutors supporting the legality of detentions. We find that "instrumental" challenges are more likely when defendants are accompanied by friends/relatives, and in the presence of more proactive judges; moreover, these challenges increase the likelihood of a ruling of illegality, controlling for other factors. However, defense practices also rely on more "expressive" challenges and other strategies that weaken the adversarial model. Critically, we also find that judicial decisions are independently shaped by the level of engagement of prosecutors during hearings and the skin color of defendants - darker defendants have lower odds of having their arrests be declared illegal. We discuss these findings in the context of the literature on courtroom workgroups and pretrial justice.